Examining The Determinants of Timeliness in Crises Policy Responses: The Case of Covid-19 In Egypt - Abdalla, Abdelhalim (AUC Knowledge Fountain, 2023)
Timely responses to crises and pandemics play a significant role in navigating and minimizing the adverse impacts of such critical periods on the public and governments worldwide. COVID-19 could show and prove how a single virus originating in a single country can rapidly spread throughout the world, transforming an epidemic in China into a global pandemic. The virus caused more than 6.5 million deaths and around 660 million confirmed cases worldwide, according to the WHO, and sparked the worst economic catastrophe globally in more than a century, as estimated by the World Bank. Evidence suggests that the extent of the crisis impacts was different across countries for several reasons, one of which was the timeliness of policy responses. However, extant research has overlooked the importance of comprehensively identifying the factors that influenced timely responses to such crises. The COVID pandemic's scope of economic and social repercussions requires a thorough understanding of timeliness in order to allow governments to prevent, contain, and mitigate its impacts on the public. This thesis fills this research gap by investigating the factors affecting the timeliness of policy responses to pandemics and crises. Using a qualitative methodology that includes document analysis, comparative case studies, and semi-structured interviews, the study proposes and explains a set of ten variables that impact the timeliness of policy responses during pandemics. Policymakers can use these proposed variables to develop, evaluate, and enhance their timeliness in responding to crises and pandemics. They can be continuously researched, developed, and refined with new findings by researchers to stand on a holistic approach to timely response to such crises. In addition, the identified variables in this thesis are applied to Egypt to stand on its timeliness in response to the ongoing crisis.